The Oxford movement: a thematic history of the tractarians and their times - Faught, C. Brad (Pennsylvania State University Press, 2003)
Politics : controversy and passion -- Religion & theology : principles and promulgation -- Friendship : fraternity and farewell -- Society : revival and reclamation -- Missions : churchmanship and bishoprics